Variation of physical wood properties and effect of dasometric variables in Ochroma pyramidale trees growing in plantation - Róger Moya; Carolina Tenorio; Verónica Villalobos-Barquero; Alejandro Meza-Montoya (Heliyon)
Physical properties were studied in commercial plantation of balsa established in Costa Rica. Among other variables studied, physical properties varied mainly for tree age, spacing, stand density, diameter, and height of trees, which we named dasometric conditions. The aim of this study was (i) to determine the variation of specific gravity (SG), air-dry density (AD), green density (GD), and green moisture content (GMC), (ii) to know the site effect and dasometric conditions on these properties, and (iii) to establish the relationship between the four physical properties. The results showed that: SG from 0.08 to 0.21, AD from 90 to 250 kg/m3, GD varied 203–274 kg/m3, and GMC from 38.8 to 137.1 %. Tree age affected statistically all physical properties, it was positively correlated with SG, AD, and GD, but negatively correlated with GMC. Diameter breast height and total height were weakly correlated with SG and AD, respectively. Commercial height and stand density were highly correlated with SG and AD, besides stand density was positively correlated with GMC. AD was positively correlated with SG and GD but negatively correlated with GMC. According to the results, balsa tree plantations exhibited significant variation in physical properties (SG, AD, GD, and GMC) in trees aged between 30 and 40 months and this variation was primarily attributed to the site-specific growth conditions, mainly temperature and precipitation. These wood properties can be selected by site and growing conditions.